Flexibility and Leadership in Start-up Culture: Employee Perspectives on Workload, Well-being, and Organizational Balance - Anwar, Mahmood (Yayasan Sinergi Kawula Muda, 2024)
Start-ups are known for their dynamic and flexible work environments, but such flexibility often comes with high workloads and intense expectations. This study investigates employee perceptions of workplace culture in Indonesian start-ups, focusing on flexibility, leadership, work-life balance, and well-being. Using a qualitative case study approach, in-depth interviews were conducted with HR professionals, executives, and employees across various start-ups. Thematic analysis identified key themes, including the dual role of flexibility as both an advantage and a challenge, the significant influence of leadership on employee satisfaction, and persistent difficulties in maintaining work-life balance. Findings indicate that while flexibility enhances innovation and employee autonomy, excessive workload and unclear boundaries often lead to stress and burnout. Leadership style plays a crucial role, as supportive leaders contribute to a positive culture, whereas high-pressure environments can negatively impact well-being. The study highlights the need for structured policies that promote both performance and employee well-being. These insights contribute to the broader understanding of start-up workplace dynamics and suggest that future research should explore cross-industry comparisons and the long-term effects of work stress in start-ups.